(untitled) (Journal of Oriental Studies, 2019)
The article discusses the requirements for the systematization of authentic texts. In addition, taking into account these requirements, within the capabilities of the University will consider ways to apply to lessons based on specific materials. Analysis of the work with a certain authentic text determines its place in the lexical aspect. The system of classification of authentic texts developed by methodologists is studied. The article also describes the ways of using technologies of working with texts. The importance of authentic texts in language learning is analyzed, the ways of their systematization are analyzed. Key words: authentic text, lexical aspect, word formation, technology of critical thinking, method of “simple” and “complex” questions, clusters, cinquain.